PENERAPAN METODE PEMBELAJARAN BRAINSTORMING DALAM MENINGKATKAN KEMAMPUAN KOGNITIF PESERTA DIDIK PADA PEMBELAJARAN FIQIH - Septiani, Widya; Kesuma, Guntur Cahaya; Asyha, Agus Faisal (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The low cognitive ability of students in Fiqh learning, particularly on the topic of bughat, remains a common issue in madrasahs. This condition is influenced by the suboptimal implementation of learning methods that encourage students’ active participation and cognitive engagement. This study is directed at describing the implementation of the brainstorming learning method in an effort to enhance students’ cognitive capacity, while also analyzing the various challenges and constraints that arise during the implementation of Fiqh instruction. This study employed a descriptive qualitative approach with a phenomenological design. The participants in this research included the Fiqh teacher, the vice principal for curriculum affairs, and Grade XI science students at MAS Muhammadiyah Sukarame Bandar Lampung. Data collection in this study was conducted through observation, interviews, documentation review, and tests to measure students’ cognitive abilities. Meanwhile, data analysis was carried out using an interactive model that includes the stages of data reduction, data display, and conclusion drawing, complemented by data validity testing through triangulation techniques. The results indicate that implementing the brainstorming method through the stages of orientation, analysis, hypothesis, incubation, synthesis, and verification improves students’ cognitive abilities. However, obstacles were identified, including differences in students’ levels of participation, limited instructional time, and classroom management issues. Therefore, systematic lesson planning is necessary to optimize students’ cognitive potential. ABSTRAK Rendahnya kemampuan kognitif peserta didik dalam pembelajaran Fiqih, khususnya pada materi bughat, masih menjadi permasalahan yang sering dijumpai di madrasah. Kondisi ini dipengaruhi oleh kurang optimalnya penerapan metode pembelajaran yang mendorong keaktifan dan keterlibatan berpikir peserta didik. Penelitian ini diarahkan untuk menguraikan implementasi metode pembelajaran Brainstorming dalam upaya meningkatkan kapasitas kognitif peserta didik, sekaligus menganalisis berbagai tantangan dan kendala yang muncul selama pelaksanaan pembelajaran Fiqih. Penelitian ini menerapkan pendekatan kualitatif deskriptif dengan desain fenomenologi. Partisipan dalam penelitian ini mencakup guru Fiqih, wakil kepala bidang kurikulum, serta peserta didik kelas XI IPA di MAS Muhammadiyah Sukarame Bandar Lampung. Pengumpulan data dalam penelitian ini dilaksanakan melalui kegiatan observasi, wawancara, studi dokumentasi, serta tes untuk mengukur kemampuan kognitif peserta didik. Sementara itu, analisis data dilakukan dengan menggunakan model interaktif yang mencakup tahapan reduksi data, penyajian data, dan penarikan simpulan, serta dilengkapi dengan uji keabsahan data melalui teknik triangulasi. Hasil penelitian menunjukkan bahwa penerapan metode brainstorming melalui tahapan orientasi, analisis, hipotesis, pengeraman, sintesis, dan verifikasi mampu meningkatkan kemampuan kognitif peserta didik. Meskipun demikian, masih ditemukan hambatan berupa perbedaan tingkat keaktifan peserta didik, keterbatasan waktu pembelajaran dan mengatur kondisi kelas. Metode brainstorming terbukti efektif meningkatkan kemampuan kognitif peserta didik dalam pembelajaran Fiqih, sehingga perencanaan pembelajaran yang sistematis diperlukan untuk mengoptimalkan potensi kognitif mereka.